2021
DOI: 10.1177/2309499020985195
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic reconstruction of the anterior cruciate ligament of the knee with or without reconstruction of the anterolateral ligament: A meta-analysis

Abstract: Purpose: To systematically analyze the effectiveness between combined anterior cruciate ligament and anterolateral ligament reconstruction (ACL+ALLR) and isolated anterior cruciate ligament reconstruction (ACLR) for treatment of patients with injured ACL. Methods: We performed a systematic search in MEDLINE, EMBASE, PubMed, Web of Science, Cochrane databases, Chinese Biomedical Literature Database, CNKI, and Wanfang Data for all relevant studies. All statistical analysis was performed using Review Manager vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
7
0
3
Order By: Relevance
“…However, knee cruciate ligament injuries are more common after a sports injury or injury from other factors. Due to the low self-healing ability of the cruciate ligament of the knee joint, after the injury, if it is not diagnosed in time and effective measures are taken to intervene, it is very easy to develop into a complete tear, which will adversely affect the stability of the joint, called secondary traumatic osteoarthropathy [ 11 ]. MRI is a commonly used imaging examination method in clinical practice; it has played a good role in the diagnosis of various diseases, it can achieve parametric and multidirectional imaging, and it has strong advantages in displaying articular cartilage and intra-articular structures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, knee cruciate ligament injuries are more common after a sports injury or injury from other factors. Due to the low self-healing ability of the cruciate ligament of the knee joint, after the injury, if it is not diagnosed in time and effective measures are taken to intervene, it is very easy to develop into a complete tear, which will adversely affect the stability of the joint, called secondary traumatic osteoarthropathy [ 11 ]. MRI is a commonly used imaging examination method in clinical practice; it has played a good role in the diagnosis of various diseases, it can achieve parametric and multidirectional imaging, and it has strong advantages in displaying articular cartilage and intra-articular structures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…30 The combination of ACLR and ALLR has shown remarkable improvement in clinical results compared with isolated ACLR. [66][67][68][69][70] Studies have shown that the most common femoral fixation sites were posterior and proximal to the lateral femoral epicondyle, and for the tibial fixation, the most common sites were between Gerdy's tubercle and the fibular head. 3,70 Regarding the graft's tension, Kunze et al, in a recent Systematic Review and Meta-Analysis of Randomized Controlled Trials, found that in 9 of 14 studies, the graft was tensioned at 30 o .…”
Section: Classification and Treatmentmentioning
confidence: 99%
“…In a recent meta-analysis, Yin et al [ 67 ] reported superior knee kinematics after combined ACLR and ALLR or LET compared to isolated ACLR in ACL deficient knees. Similarly, Littlefield et al [ 19 ] in a systematic review identified that supplementary ALLR during ACLR improved anterior tibial translation and internal knee rotation and resulted in a lower incidence of graft failure.…”
Section: Biomechanical Evaluationmentioning
confidence: 99%